2015
DOI: 10.1155/2015/481402
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Primary Vein Grafts in Free Tissue Transfers

Abstract: The outcomes of free tissue transfers combined with vein grafts have been inconsistent, and discussions continue regarding their appropriate use. Of the 142 free tissue transfers that we performed from January 2004 to December 2011, we retrospectively analyzed 15 consecutive patients who underwent free tissue transfers in combination with vein grafts. Etiologies included trauma (8 patients), infection (4), and tumor (3). Types of free tissue transfers were fibula (4), anterolateral thigh (3), groin (3), jejunu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Vascular graft implantation and bypass surgery both rely upon suture-based anastomosis. Damage to the vascular endothelium at the site of anastomosis initiates the coagulation cascade, triggers a proinflammatory response, and activates smooth muscle cells, leading to major complications such as pathological clots (thrombosis) and progressive occlusion (stenosis). Thus, there is a need for the design of bioactive sutures capable of inhibiting thrombosis and cellular activation. Another example illustrating the need for antithrombotic activity of sutures is the transplantation of tissue from one location, the “donor site”, to the desired location, the “recipient site”, with suture-based vascular anastomosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular graft implantation and bypass surgery both rely upon suture-based anastomosis. Damage to the vascular endothelium at the site of anastomosis initiates the coagulation cascade, triggers a proinflammatory response, and activates smooth muscle cells, leading to major complications such as pathological clots (thrombosis) and progressive occlusion (stenosis). Thus, there is a need for the design of bioactive sutures capable of inhibiting thrombosis and cellular activation. Another example illustrating the need for antithrombotic activity of sutures is the transplantation of tissue from one location, the “donor site”, to the desired location, the “recipient site”, with suture-based vascular anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombotic occlusion is the main cause of graft failure in free-tissue transfers, occurring in 4% of free flaps and up to 30% of digital replantation. To reduce the risk of these complications, systemic therapy with anticoagulant drugs is frequently required. ,,− Despite all these efforts, the challenge to mitigate the risk of thrombosis postsurgery still exists and needs to be addressed. , …”
Section: Introductionmentioning
confidence: 99%
“…The proximity of the DTV to the midface and scalp may avoid the need for interposition vein grafting, as a long pedicle is needed to reach veins in the neck. Single‐center studies have shown mixed results with regards to whether grafts increase the risk of flap failure, with assessment often compounded by the fact that populations requiring venous grafts have more co‐morbidities (Cheng et al, 2012; Chowlia et al, 2015; Classen, 2004; Germann & Steinau, 1996; Nemoto et al, 2015). However, avoiding the use of vein grafts can reduce operative time and potential donor site morbidity, and may reduce flap failure in the case of interposition grafts (Inbal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical regeneration of connective tissues such as vascular, tendons, and viable tissues remains a long-standing clinical challenge, primarily because insufficient treatment, repair, and even failure of injured sites by insufficient regeneration often cause unwanted inflammatory, pathological thrombosis, and progressive occlusion. , Drug-eluting surgical sutures have been commonly used as delivery depots for antibiotics, anti-inflammatory, and anesthetics at surgical sites . While adding chemical drug have repaired the injured to some extents, they are still limited by insufficiently regulating of the initial subsequent healing process.…”
Section: Introductionmentioning
confidence: 99%